The relationship between mothers' knowledge of food nutrition and the incidence of stunting at the Padang Rubek community health center - Apriani, Fitri; Satria, Orita; Susanti, Ita; Zakiyah4, Zakiyah; Aulia, Yulfa (Journal of Midwifery and Nursing, 2025)
Nutritional problems in children in Indonesia are a crucial and complex public health issue, where optimal nutrition from an early age, especially during the first 1,000 days of life (HPK), is crucial to the quality of a child's growth and development. Various forms of malnutrition, such as undernutrition, severe malnutrition, and low birth weight, are still prevalent in many regions of Indonesia. This study aims to determine the level of mothers' knowledge about nutrition and its impact on stunting rates at the Padang Rubek Health Center in 2025. The type of research used in this study is quantitative research. The research design employs a cross-sectional approach. The study population consists of 297 mothers with infants. The sampling technique used in this study is accidental sampling, with a sample size of 75 individuals. Based on the results of the statistical test using the chi-square test, a p-value of 0.002 (p<0.05) was obtained, indicating a significant association between mothers' knowledge of food nutrition and the incidence of stunting. So, there is a significant association between mothers' knowledge of food nutrition and the incidence of stunting.